(untitled) - Tricia Hedge (Oxford, 1998)
The book presents a range of writing tasks within a framework of current thinking on the process of writing. It focuses on "autoring" skills: developing a sense of audience, planning, drafting, and revising; it also considers elements of "crafting": the way in which a writer puts together the pieces of the text and chooses correct and appropriate language
Keywords: english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers,listening - problems, exercises, etc